2021
DOI: 10.1016/j.abd.2020.07.023
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophilic dermatosis of the dorsal hands related to cocaine abuse

Abstract: Neutrophilic dermatoses encompass a wide spectrum of diseases characterized by a dense infiltration mainly composed of neutrophils. Neutrophilic dermatosis of the dorsal hands is currently considered a localized variant of Sweet syndrome. Cocaine abuse has been related to a wide range of mucocutaneous manifestations, including neutrophilic dermatoses such as pyoderma gangrenosum. The authors of this study present a patient with neutrophilic dermatosis of the dorsal hands, in which cocaine abuse was identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Accordingly, the classic differential diagnoses of cocaine-related skin diseases include various neutrophilic disorders, such as cocaine-induced midline destructive lesions, ANCA-associated vasculitis-retiform purpura/cocaine-levamisole–associated autoimmune syndrome (CLAAS), pyoderma gangrenosum, pyostomatitis vegetans and neutrophilic dermatosis of the dorsal hands (eFigure 1 in Supplement 1). For all of them, neutrophils, vasculitis, and intravascular thrombotic phenomena in the results of biopsy are diagnostic hallmarks.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the classic differential diagnoses of cocaine-related skin diseases include various neutrophilic disorders, such as cocaine-induced midline destructive lesions, ANCA-associated vasculitis-retiform purpura/cocaine-levamisole–associated autoimmune syndrome (CLAAS), pyoderma gangrenosum, pyostomatitis vegetans and neutrophilic dermatosis of the dorsal hands (eFigure 1 in Supplement 1). For all of them, neutrophils, vasculitis, and intravascular thrombotic phenomena in the results of biopsy are diagnostic hallmarks.…”
Section: Discussionmentioning
confidence: 99%
“…It is abused due to its ability to induce intense euphoria, increase energy, and enhance sociability. This illicit use carries significant health and legal risks including myocarditis, arrhythmia, hypertension, or heart failure. , When considering the way of administration of the above-considered drugs, it may be found that AMP, mAMP, and COC are mostly abused via oral administration, injection, or snorting, whereas in the case of MDMA, oral administration and snorting are mostly practiced. The latter is abused in the form of powder, colloquially called “molly” and is characterized by rapid and intense action usually accompanied by colored visual effects …”
Section: Introductionmentioning
confidence: 99%